Modelo Customer Relationship Management para el mejoramiento de la gestión de la Empresa Turística Macobar Compañía Limitada, en la ciudad de Guaranda, provincia Bolívar, año 2023 - Paredes Saltos, Verónica Mercedes (2023)
In the present research work is developed in the tourist company Macobar limited company, which is located in the province of Bolívar in the city of Guaranda, year 2023. In the Macobar company, there was no Customer Relationship Management model that would help it to have direct customer service, a database or loyalty, and this avoids having an improvement in management. According to the problem that has been found in the company, a Customer Relationship Management model has been proposed as a general objective of the investigation, to guarantee a better relationship with customers, generate a database, more striking and efficient advertising, to generate fidelity with customers generating an improvement in management. For the execution of the present study, field, historical, descriptive and inferential research was used, with a quantitative and qualitative approach, the deductive method was applied, in addition, for the collection of information, a survey directed to the users of the company was carried out. Macobar and an interview was conducted with the manager of the company for an internal and external analysis. The project is feasible because the Customer Relationship Management model provides a database, customer service, marketing campaign on social networks, loyalty, thus improving the management of the company. Key Words: Model, CRM, Improvement, Management